Optimasi Kit Zeesan SARS-COV-2 Test Kit untuk Pengujian Deteksi DNA Porcine pada Produk Olahan Daging dan Produk Olahan Kompleks: Optimization of Zeesan SARS-COV-2 Test Kit for Porcine DNA Detection Tests on Processed Meat Products and Complex Processed Product - Tirta Setya Bhakti (FKIP, Universitas Palangka Raya, 2022)
Various brands of covid 19 RNA detection kits are widely used by covid 19 testing laboratories. One of these kits is the Zeesan SARS COV-2 Test Kit. The Zeesan kit cannot be used to detect porcine DNA. There has been no official research on the use of optimized covid 19 detection kits for porcine DNA detection, thus the optimization of the Zeesan SARS COV-2 Test Kit used to detect porcine DNA is a new innovation in molecular testing. The purpose of this study was to find the right combination between the Zeesan SARS COV-2 Test Kit detection kit and the porcine primer-probe. Then look for the appropriate temperature setting for the amplification process for porcine DNA testing. Analysis using Liferiver brand real-time PCR with hydrolysis probe method. The study was conducted by running 3 types of positive porcine samples with 3 different concentrations. The research sample used sausage, ham, and noodles. The results showed that the combination detection kit of Zeesan SARS COV-2 Test Kit-primary probe porcine successfully detected porcine DNA in 3 positive samples of porcine with a concentration of 10 ng and 5 ng. Meanwhile, at a concentration of 1 ng, it could only be detected in 2 positive samples. In addition, this study showed a relatively faster detection time of porcine DNA than several previous studies.